2019
DOI: 10.1080/2162402x.2019.1621677
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an interferon signature predicting prognosis and treatment response for glioblastoma

Abstract: Background: Interferon treatment, as an important approach of anti-tumor immunotherapy, has been implemented in multiple clinical trials of glioma. However, only a small number of gliomas benefit from it. Therefore, it is necessary to investigate the clinical role of interferons and to establish robust biomarkers to facilitate its application. Materials and methods: This study reviewed 1,241 glioblastoma (GBM) and 1,068 lower grade glioma (LGG) patients from six glioma cohorts. The transcription matrix and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…Studies that evaluated infiltration of malignant gliomas by NK cells have reported different findings, ranging from the presence of insignificant NK cell numbers to large NK cell infiltrates in up to 89% of glioblastomas (26, 27). Another study described less infiltration of high-risk gliomas with NK cells and M1-like macrophages than lower grade gliomas (28). Therefore, differences in the subtype and stage of the disease, treatment history and permeability of the blood-brain barrier (BBB) appear to affect the likeliness of infiltration by NK cells.…”
Section: Nk Cells In the Tumor Microenvironment Of Glioblastomamentioning
confidence: 99%
“…Studies that evaluated infiltration of malignant gliomas by NK cells have reported different findings, ranging from the presence of insignificant NK cell numbers to large NK cell infiltrates in up to 89% of glioblastomas (26, 27). Another study described less infiltration of high-risk gliomas with NK cells and M1-like macrophages than lower grade gliomas (28). Therefore, differences in the subtype and stage of the disease, treatment history and permeability of the blood-brain barrier (BBB) appear to affect the likeliness of infiltration by NK cells.…”
Section: Nk Cells In the Tumor Microenvironment Of Glioblastomamentioning
confidence: 99%
“…In recent years, the secretome of cancer cells and its impact on therapy response has gained attention and numerous studies explore its role in several aspects of tumour including in which compartment of the tumour this pathway is activated. Moreover, high expression of interferon-regulated genes in several tumour entities also strongly correlated with a worse outcome in patients 37,38 . All of these studies highlight the high degree of plasticity of type I IFN and the need for a better understanding of the role of this pathway in the context of cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Immunomodulation with checkpoint inhibitors is considered to belong to the domain of tumor-agnostic treatments [ 47 ]. Immunotherapies generally do not point to the molecular biological characteristics inside tumor cells, but, rather, to the surface of tumor cells, including a heterogeneous number of known and unknown tumor antigens [ 67 ] and immune costimulatory and inhibitory molecules on the surface [ 68 , 69 , 70 ], as well as the production of cytokines and chemokines that influence the immune system and the inflammatory response [ 71 ]. Terms like “cold” versus “hot” tumors, describing differences in lymphocyte infiltration in the tumor microenvironment, have become highly relevant [ 72 ].…”
Section: Immunotherapy For Gbmmentioning
confidence: 99%